Pengembangan Getah Pepaya, Ekstrak Pepaya (Carica papaya L.) dan Ekstrak Umbi Bengkuang (Pachyrrhizus erosus (L.) Urb.) untuk Lotion Pencerah Kulit Berdasar Aktivitas Antioksidan dan Inhibisi Tirosinase - LEONARDUS BROTO SUGENG KARDONO; LIANDHAJANI LIANDHAJANI; NINA ARTANTI; YETI MULYATI ISKANDAR; SITI MASRURAH BROTO SUTARYO (Fakultas Farmasi Universitas Pancasila, 2013)
Whitening or skin lightening products are well known as cosmetic. In this development, papaya latex (Carica papaya L.), papaya fruit extract and yam bean tuber extracts (Pachyrrhizus erosus (L.) Urb.) were combined for skin lightening body lotion formula. Antioxidant and tyrosinase inhibitory activities were evaluated in the starting materials and the products. Antioxidant activity evaluation was conducted using DPPH free radical scavenging activity method. Tyrosinase inhibitory evaluation was performed based on tyrosinase enzymatic inhibitory reaction to tyrosine as substrate. Papaya latex showed the highest antioxidant activity (32.01%), followed by yam bean tuber extract (27.04%) and papaya extract (26.09%). The tyrosinase inhibitory activities of papaya latex, papaya fruit extract and yam bean tuber extracts were 68.42 %, 36.80% and 52.63 % respectively, as compared to that of arbutin (100%). Based on product appearance, color, odor, pH and viscosity, the product were stable for 128 weeks. The expired date calculation on its antioxidant activity, however, the product was stable for 77 weeks. It is recommended that the product should be stored in non transparent bottle at low temperature or at about 25-28oC.